Efek Aktivasi H2SO4 Terhadap Lempung Sebagai Katalis Dalam Pembuatan Biodiesel Dari Crude Palm Oil (CPO) - Muhammad Disro; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Indonesia petroleum consumed are increasing, while hot Indonesia's petroleum reserves are depleting so that fuel substitution needs to be sought. Recent years, a lot of research has done, purposed to find an alternative source one of that is biodiesel. Raw material for biodiesel production can be from animal fat or vegetable oil. Crude palm oil (CPO) one of an alternative raw material. This research is aimed to produce biodiesel from CPO, studying factors which influences production process, such as catalyst, recycle and regeneration as well as to determine the physical and chemical properties of biodiesel produced. The transesterification process was done, a mole ratio of oil: methanol 1: 9, oil mass 50 grams, weight of the catalyst 1%-wt, having temperature of 60°C for 90 minutes. Clay catalysts are activated with acids, and then recycle and regeneration of catalyst. Result given by of alkaline activation of the catalyst 90.16%. Based on characterization of physical properties of biodiesel, result as follow density 0.869 g/ml, kinematic viscosity 4,65 mm2/s, the flash point 120oC and cetane number 51,74. The catalyst regeneration proved not a 100% of catalyst reactived.Keywords: biodiesel, clay, recycle, regeneration, transesterification